Planning Land Needs And Suitability Levels Complete Facilities And Comfort Terminal Kunjang River In The City Of SAMARINDA - FRY, JEF (KURVA S JURNAL MAHASISWA, 2014)
One of the terminals in the city of Samarinda Kunjang River Terminal . This terminal is located on Jl . Fortunately Suropati , Coral Acid Ulu . This terminal to accommodate large buses serving the route Samarinda - Balikpapan and the buses are serving the route Samarinda to several districts in Kutai regency upstream, such as City Build , Muara Kaman , Senoni , as well as to the West Kutai like Melak or Cape Isuy . According to data Bappeda and Samarinda city master plan Kunjang River Terminal has an area of approximately 906 m2 and ± 193,876 / year the number of passengers departing from this terminal . The purpose of this study is to evaluate the capacity of the terminal to the parking needs Kunjang River . The purpose of this study is as follows :Knowing the volume of parking for buses , public transportation and cars ( introduction and pickup ) in the river terminal KunjangKnowing the accumulation of parking for buses , public transportation and cars ( introduction and pickup ) in the river terminal KunjangKnowing parking duration ( Duration ) for buses , public transportation and cars ( introduction and pickup ) in the river terminal Kunjang Based on the results of the discussion it can be concluded for the evaluation of parking in Samarinda Kun.jang River Terminal is The volume of river park at terminal Kunjang for some kind of vehicle functions such as : Bis AKDP average daily volume of vehicles out from 75.43 to 75 units , vehicles entering from 46.71 to 47 units , the volume of 800.71 to 801 units . Public transportation average daily volume of vehicles out 140.86 to 141 units , vehicles entering from 125.57 to 126 units , the volume of 580.57 to 581 units . Four wheels ( introduction and pickup ) , the average daily volume of vehicles out 107.29 to 107 units , vehicles entering from 105.14 to 105 units , the volume of 235.14 to 235 units . Accumulation in the terminal parking Kunjang River for some kind of vehicle functions such as : Bus AKDP average obtained for the accumulation of 725.29 to 725 units , public transportation to the average obtained by the accumulation of 739.71 to 740 units , four wheels ( introduction and pickup ) to the average obtained by the accumulation of 127.86 to 128 units . Parking long time ( duration ) in the terminal parking Kunjang River for some kind of vehicle functions such as : Bus AKDP obtained for the average duration of 90.90 minutes , public transportation and to obtain an average duration of 90.19 minutes , four wheels ( introduction and pickup ) to obtain an average duration of 89.78 minutes